Approximations by Fourier Sums on the Sets $L^{ψ} L^{P(∙)}$ - Chaichenko, S. O. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study some problems of imbedding of the sets of $ψ$-integrals of the functions $f \in L^{p(∙)}$ and determine the orders of approximations of functions from these sets by Fourier’s sums.